A comparison study on the anti-leech effects of onion (Allium cepa L) and ginger (Zingiber officinale) with levamisole and triclabendazole - Bahmani Mahmoud; Vakili-Saatloo Naiema; Gholami-Ahangaran Majid; Karamati Seyed Ahmad; Banihabib Ebrahimkhalil; Hajigholizadeh Ghader; Borjian Sayfollah (Shahrekord University of Medical Sciences, 2013)
Introduction: Leech may indwell in mucosa of the pharynx, tonsil, esophagus, nose, nasopharyngeal and rarely in larynx of hosts, however, the effective drugs against this parasite is scarce. This study was aimed to evaluate and compare the anti-leech effect of methanolic extract of onion (Allium cepa L) and ginger (Zingiber officinale) with levamisole and triclabendazole. Materials and Methods: In this study, 60 leeches (Limnatis nilotica) were collected from south of Ilam. The anti-leech effect of methanolic extract of onion and ginger in comparison with levamisole and triclabendazole drugs (positive controls) were evaluated. Distilled water was used as negative control. Paralysis and death of leeches were recorded in 720 minutes. Results: Lethal effect of methanolic extract of ginger against Limnatis nilotica was equal to levamisole and more than triclabendazole and methanolic extract of onion. Conclusion: Ginger equal to levamisole has anti-leech activity and its methanolic extract might be used against Limnatis nilotica.